AutoMedic: Framework of Automatic Pill Dispenser System with Human Centered Design Method - Hidayat, Muhammad Luqman; Irianto, Kurniawan D (International Journal of Informatics and Computation, 2025)
Medication non-adherence is a serious problem in Indonesia, with low adherence rates reaching 41.5% in hypertension patients and 78.1% in type 2 diabetes mellitus patients, due to memory loss, complexity of medication schedules, and physical limitations, especially in the elderly population. This study aims to develop an IoT-based automatic pill medicine dispenser to improve medication adherence through a Human Centered Design approach that focuses on user needs. The research methodology uses three stages of HCD: Inspiration through in-depth interviews with users of various ages and health experts, Ideation to design a system concept that integrates ESP32, RTC DS3231, servo motor, and mobile application with Firebase as a real-time database, and Implementation to develop functional prototypes and usability evaluation. The test results show that the system can function well in providing reminder notifications, automatic dispensing, and real-time monitoring of medicine consumption. Evaluation with ten respondents showed good ease of use, although elderly users had difficulty in setting schedules through the application and needed improvements in portability and notification customization. This research contributes user-friendly health technology solutions and an HCD-based IoT development framework to improve medication adherence in patients with chronic diseases.